3D design of heterogeneous catalytic biodiesel reactor and its plant using Aveva PDMS - Muhamad Akmal, Muhamad Yusuf (2013)
The research focuses on how to design a 3D model of the heterogeneous catalytic biodiesel reactor and its plant by using AVEVA PDMS software. The scope of the research firstly was to model the heterogeneous catalytic biodiesel plant for production of biodiesel according to F3 factory concept. Then, produce a detail piping and instrumentation diagram (P&ID) of the plant and lastly simulate the design of the plant in 3D drawing by using AVEVA PDMS software. In this research, batch system is chosen due to its flexibility and follows F3 factory concept and the plant was built on the container truck. The methodology of the research was designing according to the piping and instrumentation diagram (P&ID). Then, sizing of the equipment and mechanical design and lastly involve 3D simulation. For the result a 3D design of heterogeneous catalytic biodiesel reactor and its conceptual design of the biodiesel plant are by using AVEVA PDMS was achieved. Lastly, the importance of the research is to fulfill the industrial demand on 3D design and showing it to be as the best way to review the plant layout and how to manage the plant because it contains all specification such as measurement, material selection and already visualize. Meanwhile, 3D design is also used for pipe checking to avoid clash of pipe.